Endothelin Receptor Antagonism Improves Lipid Profiles and Lowers PCSK9 (Proprotein Convertase Subtilisin/Kexin Type 9) in Patients With Chronic Kidney Disease. Issue 2 (August 2019) - Farrah, Tariq E.; Anand, Atul; Gallacher, Peter J.; Kimmitt, Robert; Carter, Edwin; Dear, James W.; Mills, Nicholas L.; Webb, David J.; Dhaun, Neeraj
Abstract : Dyslipidemia is common in chronic kidney disease (CKD). Despite statins, many patients fail to adequately lower lipids and remain at increased risk of cardiovascular disease. Selective ETA (endothelin-A) receptor antagonists reduce cardiovascular disease risk factors. Preclinical data suggest that ETA antagonism has beneficial effects on circulating lipids. We assessed the effects of selective ETA antagonism on circulating lipids and PCSK9 (proprotein convertase subtilisin/kexin type 9) in CKD. This was a secondary analysis of a fully randomized, double-blind, 3-phase crossover study. Twenty-seven subjects with predialysis CKD on optimal cardio- and renoprotective treatment were randomly assigned to receive 6 weeks dosing with placebo, the selective ETA receptor antagonist, sitaxentan, or long-acting nifedipine. We measured circulating lipids and PCSK9 at baseline and then after 3 and 6 weeks. Baseline lipids and PCSK9 did not differ before each study phase. Whereas placebo and nifedipine had no effect on lipids, 6 weeks of ETA antagonism significantly reduced total (−11±1%) and low-density lipoprotein–associated (−20±3%) cholesterol, lipoprotein (a) (−16±2%) and triglycerides (−20±4%); high-density lipoprotein–associated cholesterol increased (+14±2%), P <0.05 versus baseline for all. Additionally, ETA receptor antagonism, but neither placebo nor nifedipine, reduced circulating PCSK9 (−19±2%; P <0.001 versus baseline; P <0.05 versus nifedipine and placebo). These effects were independent of statin use and changes in blood pressure or proteinuria. Selective ETA antagonism improves lipid profiles in optimally-managed patients with CKD, effects that may occur through a reduction in circulating PCSK9. ETA receptor antagonism offers a potentially novel strategy to reduce cardiovascular disease risk in CKD. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00810732. Abstract : Supplemental Digital Content is available in the text.